MR-Guided Adaptive Radiotherapy for Bladder Cancer - Hijab, Adham; Tocco, Boris; Hanson, Ian; Meijer, Hanneke; Nyborg, Christina Junker; Bertelsen, Anders Smedegaard; Smeenk, Robert Jan; Smith, Gillian; Michalski, Jeff; Baumann, Brian C.; Hafeez, Shaista (Frontiers in Oncology, 2021)
Radiotherapy has an important role in the curative and palliative treatment settings for bladder cancer. As a target for radiotherapy the bladder presents a number of technical challenges. These include poor tumor visualization and the variability in bladder size and position both between and during treatment delivery. Evidence favors the use of magnetic resonance imaging (MRI) as an important means of tumor visualization and local staging. The availability of hybrid systems incorporating both MRI scanning capabilities with the linear accelerator (MR-Linac) offers opportunity for in-room and real-time MRI scanning with ability of plan adaption at each fraction while the patient is on the treatment couch. This has a number of potential advantages for bladder cancer patients. In this article, we examine the technical challenges of bladder radiotherapy and explore how magnetic resonance (MR) guided radiotherapy (MRgRT) could be leveraged with the aim of improving bladder cancer patient outcomes. However, before routine clinical implementation robust evidence base to establish whether MRgRT translates into improved patient outcomes should be ascertained.